Rape Myth Acceptance in a Community Sample of Adult Women in the Post #MeToo Era - PettyJohn, Morgan E. (Journal of interpersonal violence, 2023)
Rape myth acceptance (RMA) is commonly targeted in anti-rape activism (e.g., the #MeToo Movement) and prevention work due to its association with perpetration, risk of victimization, survivor outcomes, and injustices in the criminal legal system. The 22-item updated Illinois Rape Myth Acceptance (uIRMA) scale is a widely used, reliable measure for assessing this construct; however, it has primarily been validated within samples of U.S. college students. To assess the factor structure and reliability of this measure for community samples of adult women, we analyzed uIRMA data from 356 U.S. women (age 25–35) collected via CloudResearch’s MTurk toolkit. Confirmatory factor analysis demonstrated high internal reliability for the overall scale (α = .92) and supported a five-factor structure (subscales: She Asked For It, He Didn’t Mean To, He Didn’t Mean To [Intoxication], It Wasn’t Really Rape, She Lied) with good model fit. The rape myth ‘‘He Didn’t Mean To’’ was most highly endorsed in the overall sample, while ‘‘It Wasn’t Really Rape’’ was endorsed the least. Analyses of RMA and participant characteristics demonstrated that women identifying as politically conservative, religious (predominantly Christian), or heterosexual endorsed rape myth constructs at significantly higher rates. Education level, social media use, and victimization history yielded mixed findings across RMA subscales, while age, race/ethnicity, income level, and regional location showed no associations with RMA. Findings suggest the uIRMA is an appropriate measure of RMA in community samples of adult women; however, the field would benefit from more consistent administration of the scale (i.e., 19-item vs. 22-item version; directionality of Likert-type scale) to allow for comparability across time and samples. Rape prevention work should target ideological adherence to patriarchal and other oppressive belief systems which may represent a common underlying factor across groups of women showing higher endorsement of RMA.